THE EFFECTIVENESS OF USING GUIDED DISCOVERY METHOD IN NAHWU LEARNING AT SMP-IT IZZATUNA PALEMBANG - Ica Amelia; Munirul Abidin (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2024)
The study examines the effectiveness of the guided discovery method on the learning of nahwu in the VIII grade at SMPIT Izzatuna Palembang. In addition, there is a problem of low motivation and enthusiasm in learning Nahwu using the old methods. Nahwu is considered to be a difficult and exhausting lesson, so innovation in the methods of learning is required. With the guided discovery method, students are expected to be able to find the structure of Arabic words in learning nahwu, and is expected to make learners more active and creative in the learning process, where teachers act as facilitators that direct and guide them—research using a quasi-experimental approach with a sample of 34 students. The data collection used pre-test and post-test results. The analysis methods used were descriptive tests, homogeneity tests, normality tests, paired sample T-tests, independent sample t-tests, and N-Gain tests. The research results concluded that the guided discovery method can improve learning outcomes, interest, and motivation of students toward Nahwu learning. This is evident from the average results obtained by the experimental class, which was 80, better and more effective compared to the control class, which obtained an average result of 60 using the Istiqroiyah method. From the average results, the guided discovery method can improve learning outcomes by 20 points.